Development of the Next Generation Sequencing-Based Diagnostic Test for β-Thalassemia and its Validation in a Pashtun Family. (3rd July 2020) - Sabiha, Bibi; Haider, Syed Adnan; Jan, Hanifullah; Yousafzai, Yasar Mehmood; Afridi, Ome Kalsoom; Khan, Abid Ali; Ali, Johar
Abstract: β-Thalassemia (β-thal) is a common monogenic disease with ethnic-specific mutations on the HBB gene throughout the world. The reported mutations either reduce the expression or completely inactivate the HBB gene. In Pakistan, the prevalence of β-thal is high due to consanguineous marriages. Accurate identification of mutations in carriers is imperative for prevention of β-thal in subsequent generations. To overcome the limitations of traditional testing methods for β-thal, a next-generation sequencing (NGS)-based diagnostic test was designed and validated by sequencing the entire HBB gene. The primer set covering the entire HBB gene was designed and validated in a Pashtun β-thalassemic family. The polymerase chain reaction (PCR) product was sequenced using an Illumina MiSeq platform. A homozygous pathogenic insertion of A>AC/AC (rs35699606) was detected in an affected member of the family, while unaffected members were heterozygous for it. In addition, all family members were homozygous for the synonymous variant, A>G/G (rs713040), except the father who was heterozygous for it. We sequenced the entire HBB gene using the NGS-based test, which is highly sensitive, robust and specific for the diagnosis and screening of β-thal in Pakistan, especially for families practicing consanguineous marriages.